1999
DOI: 10.1002/(sici)1098-2744(199907)25:3<207::aid-mc7>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of ?-catenin in normal and carcinogenic endometrium

Abstract: We have previously shown that the connexin (Cx) 26 and 32 genes are expressed during the secretory phase of the human endometrium and that their expression is downregulated during the proliferative phase, suggesting a role for intercellular transduction in cell growth control in human endometrium. To further study the possible role of cell-to-cell interaction in growth regulation, we immunohistochemically analyzed 80 endometrial samples (30 of normal endometrium, 20 of endometrial hyperplasia, and 30 of endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
2
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 26 publications
7
75
2
2
Order By: Relevance
“…In the current study, cytoplasmic and cell border staining of the overlying epithelium (OSE) was present, while nuclear staining was absent. Nuclear APC staining has been described in the uterus using the same antibody as in this study (Nei et al, 1999). We believe that APC was not truncated in the normal ovary or in the normal colon sample since the immunoblot demonstrated a band at the expected size of 312 kDa (Smith et al, 1993).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the current study, cytoplasmic and cell border staining of the overlying epithelium (OSE) was present, while nuclear staining was absent. Nuclear APC staining has been described in the uterus using the same antibody as in this study (Nei et al, 1999). We believe that APC was not truncated in the normal ovary or in the normal colon sample since the immunoblot demonstrated a band at the expected size of 312 kDa (Smith et al, 1993).…”
Section: Discussionsupporting
confidence: 67%
“…Others, as well as the results of this study, have revealed that bcatenin is localised at the cell borders and not in the nucleus of normal OSE or OSE lining the inclusion cysts (Davies et al, 1998). However, nuclear b-catenin has been described in normal cells of other organs such as the endometrium of the uterus (Nei et al, 1999). Mutations in the b-catenin gene are infrequent in ovarian carcinoma and interestingly only described in the endometrioid type of epithelial ovarian tumours (Palacios and Gamallo, 1998;Wright et al, 1999).…”
Section: Discussioncontrasting
confidence: 41%
“…Nei et al found that strong nuclear staining of ␤-catenin was more frequent in endometrial hyperplasia than in endometrial carcinoma samples, suggesting a role in the early development of this tumor type. 49 Their study did not show any correlation between the presence of hyperplasia and expression of ER, suggesting that the CTNNB1/wnt-1 signaling pathway is activated irrespective of ER stimulation. In another study, two endometrial tumors with ␤-catenin mutations had adjacent hyperplasia with wild0type ␤-catenin, suggesting a role of ␤-catenin activation in the transition from benign to malignant phase, though not necessarily a gatekeeper-type event, in endometrial tumorigenesis.…”
Section: Discussionmentioning
confidence: 86%
“…[12][13][14]22,23 Abnormalities of b-catenin have also been shown in a significant proportion of endometrial neoplasms. 3,5 Mutations have been recorded in 13-31% cases and appear more common in lowgrade endometrioid adenocarcinomas, [31][32][33][34][35][36] whereas an abnormal immunolocalization in the form of reduced membrane staining with diffuse cytoplasmic and/or nuclear staining has been recorded in 25-76% cases. [34][35][36][37][38][39] Most b-catenin mutations lead to decreased protein degradation and are associated with altered (usually nuclear) immunoreactivity.…”
Section: Endometrial Carcinoma Invasionmentioning
confidence: 99%
“…3,5 Mutations have been recorded in 13-31% cases and appear more common in lowgrade endometrioid adenocarcinomas, [31][32][33][34][35][36] whereas an abnormal immunolocalization in the form of reduced membrane staining with diffuse cytoplasmic and/or nuclear staining has been recorded in 25-76% cases. [34][35][36][37][38][39] Most b-catenin mutations lead to decreased protein degradation and are associated with altered (usually nuclear) immunoreactivity. 32,35 However, the converse is not always true as dysregulation of many other factors can lead to the abnormal localization of b-catenin, reflecting the multiple pathways that control the distribution and metabolism of this protein.…”
Section: Endometrial Carcinoma Invasionmentioning
confidence: 99%